A diverse family of bacterial deubiquitinases is defined by the Coxiella burnetii effector EmcB - Jeffrey K. Duncan-Lowey; Craig R. Roy (Proceedings of the National Academy of Sciences, 2025)
The obligate intracellular pathogen Coxiella burnetii encodes a deubiquitinase called EmcB that prevents signaling by the host immune sensor Retinoic acid Inducible Gene I (RIG-I). The evolutionary relationship between EmcB and other deubiquitinases is currently unknown. Here, we show that EmcB defines a broad family of bacterial deubiquitinases divergently evolved from the eukaryotic Ovarian Tumor (OTU) family of deubiquitinases. Our data indicate that the emcB gene has an internal gene rearrangement that resulted in a circular permutation of the OTU fold. Proteins with a region homologous to the deubiquitinase domain of EmcB were identified in numerous members of the bacterial order Legionellales. Proteins with an EmcB-related deubiquitinase domain demonstrated cysteine protease activity that cleaved ubiquitin and ubiquitin-related modifiers. Most of the bacteria encoding EmcB-related proteins had components of the Dot/Icm Type IVB secretion system that delivers EmcB into host cells. Indeed, many of these EmcB-related proteins were translocated into eukaryotic cells by the Dot/Icm system of Legionella pneumophila , consistent with their predicted roles as bacterial effector proteins that target host pathways. Comparison of EmcB family deubiquitinases revealed a two-domain architecture of EmcB comprising a deubiquitinase domain and a ubiquitin binding module that confers enzyme specificity for certain polyubiquitin chains. This ubiquitin binding region in EmcB was found to be necessary for efficient inhibition of RIG-I signaling. Thus, these EmcB-related proteins represent a large family of deubiquitinating enzymes that arose by divergent evolution in Legionellales , likely enabling these bacteria to infect different host cells by targeting signaling pathways regulated by ubiquitin.